2018
DOI: 10.1080/2000656x.2018.1444618
|View full text |Cite
|
Sign up to set email alerts
|

Does postauricular fascial flap reduce suture complications in otoplasty?

Abstract: Numerous suture techniques and covering flaps have been described to minimize complications related to sutures in otoplasty. The split postauricular fascial flap is one of such techniques, and it has been used to pad otoplasty suture. The aim of this study was to evaluate complications related to nonabsorbable cartilage sutures in otoplasty, using a variation of the split postauricular fascial flap. In this retrospective case series, we analyzed otoplasty patients in whom simplified split postauricular fascial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Postauricular adipofascial flaps have been described to provide additional soft tissue coverage of Furnas and Mustardé sutures. 1 , 4 , 14 Horlock et al 16 and Irkoren et al 17 did not report any suture extrusion events following the use of postauricular adipofascial flaps in 51 and 100 cases, respectively. However, other studies have tried to replicate these findings, with suture extrusion and recurrence rates of 2.64% 14 and 4.8%, 18 respectively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Postauricular adipofascial flaps have been described to provide additional soft tissue coverage of Furnas and Mustardé sutures. 1 , 4 , 14 Horlock et al 16 and Irkoren et al 17 did not report any suture extrusion events following the use of postauricular adipofascial flaps in 51 and 100 cases, respectively. However, other studies have tried to replicate these findings, with suture extrusion and recurrence rates of 2.64% 14 and 4.8%, 18 respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Prominent ear is the most frequent congenital external ear deformity, affecting roughly 5% of the general population. 1 3 Although the deformity presents with no functional problems, the condition often has significant psychological and social impacts on the patient, especially in children. 4 6 As such, otoplasty has become one of the most common aesthetic operations in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Our complications including hematoma (1.25% of the ears), perichondritis (1.25% of the patients), and hypertrophic scars (2.5% of the ears) were at a quite acceptable rate compared with other cartilage-sparing techniques. 11,12,22,23 We attribute this to our meticulous dissection and bleeding control. We observed no wound infection or skin necrosis in any of our cases.…”
Section: Discussionmentioning
confidence: 93%
“…Although we did not use a posterior facial flap technique, we had a similar rate of suture extrusion complications (2.5% of the ears) compared to the other studies using facial flaps, which reported complication rates ranging from 0% to 7.3%. 11,22,23 We presume that the vascularization of skin flap and flap thickness were not changed since we undermined the postauricular skin flap in the subdermal plane by cold dissection. This preservation as well as the suture materials we used were effective in our success.…”
Section: Discussionmentioning
confidence: 99%